Optimizing Digital Branding to Strengthen Brand Identity in Islamic Schools: A Study of MAN 2 Tulungagung - Sukarji Sukarji; Zuhri Zuhri (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2024)
This study examines optimizing digital branding to enhance brand identity at Islamic educational institutions, specifically at MAN 2 Tulungagung. This research employs a qualitative approach. Data collection techniques include participant observation, in-depth interviews, and documentation. The data analysis process involves data condensation, data display, and concluding. The findings indicate that digital branding is optimized through various digital platforms such as Instagram, TikTok, the official website, and WhatsApp Groups to reach a broader audience. Social media builds public awareness and interest in the school's strengths by presenting engaging and informative visual content. Moreover, the official website is a transparent and publicly accessible formal communication channel. This digital branding strategy has successfully increased the number of new applicants, especially in the school's flagship programs in arts and sports, which serve as the unique identity of MAN 2 Tulungagung. The school's brand identity is closely tied to its strong commitment to Islamic values, reflected in the curriculum and other flagship programs. However, digital branding optimization faces several challenges, including limited human resources—relying on only one staff member to manage multiple digital platforms—and internal coordination issues caused by sudden schedule changes. MAN 2 Tulungagung has planned training programs to address these challenges to improve staff competence in information technology management and strengthen their ability to operate various digital platforms effectively. This study has implications that optimizing branding digitalization can increase public awareness and interest in the excellence of madrasahs, thereby increasing the number of new registrants. However, there are challenges in its implementation, such as limited human resources and internal coordination.